Slide 72
Slide 72 text
Proof tricks
Rice method : notation
We start with some notation. Let
z(1) = (z(1)
−fc
, . . . , z(1)
0
, . . . , z(1)
fc
),
z(2) = (z(2)
−fc
, . . . , z(2)
0
, . . . , z(2)
fc
) ,
be i.i.d Nn
(0, Idn
) random vectors. Set, for any t ∈ [0, 1],
X(t) = z(1)
0
+
fc
k=1
(z(1)
k
+ z(1)
−k
) cos(2πkt) +
fc
k=1
(z(2)
−k
− z(2)
k
) sin(2πkt) ,
Y (t) = z(2)
0
+
fc
k=1
(z(2)
k
+ z(2)
−k
) cos(2πkt) +
fc
k=1
(z(1)
k
− z(1)
−k
) sin(2πkt) ,
Z(t) = X(t) + ıY (t) .
Then, note that
σ0
Z ∞
d
= F∗
n
(ε) ∞
and sup
t∈[0,1]
|Z(t)|
√
n( z(1) 2
2
+ z(2) 2
2
)1
2
d
=
F∗
n
(ε) ∞
√
n ε 2
,
where σ0 > 0 is the (unknown) standard deviation of the noise ε.